Buyang huanwu decoction inhibits diabetes-accelerated atherosclerosis via reduction of AMPK-Drp1-mitochondrial fission axis. (10th August 2023) - Tong, Wanyu; Leng, Ling; Wang, Yucheng; Guo, Jingwen; Owusu, Felix Boahen; Zhang, Yue; Wang, Fang; Li, Ruiqiao; Li, Yuhong; Chang, Yanxu; Wang, Yuefei; Wang, Qilong
Abstract: Ethnopharmacological relevance: Traditional Chinese drugs, including Buyang Huanwu decoction (BYHWD), have been used in traditional practice to manage cardiovascular and cerebrovascular diseases. However, the effect and mechanisms by which this decoction alleviates diabetes-accelerated atherosclerosis are unknown and require exploration. Aim of the study: This study aims to investigate the pharmacological effects of BYHWD on preventing diabetes-accelerated atherosclerosis, and elucidate its underlying mechanism. Materials and methods: Streptozotocin (STZ)-induced diabetic ApoE −/− mice were treated with BYHWD. Atherosclerotic aortic lesions, endothelial function, mitochondrial morphology, and mitochondrial dynamics-related proteins were evaluated in isolated aortas. High glucose-exposed human umbilical endothelial cells (HUVECs) were treated with BYHWD and its components. AMPK siRNA transfection, Drp1 molecular docking, Drp1 enzyme activity measurement, and so on were used to explore and verify the mechanism. Result: BYHWD treatment inhibited the worsening of diabetes-accelerated atherosclerosis by lessening atherosclerotic lesions in diabetic ApoE −/− mice, by impeding endothelial dysfunction under diabetic conditions, and by inhibiting mitochondrial fragmentation by lowering protein expression levels of Drp1 and mitochondrial fission-1 protein (Fis1) in diabetic aortic endothelium. In high glucose-exposed HUVECs, BYHWD treatment also downgraded reactive oxygen species, promoted nitric oxide levels, and abated mitochondrial fission by reducing protein expression levels of Drp1 and fis1, but not mitofusin-1 and optic atrophy-1. Interestingly, we found that BYHWD's protective effect against mitochondrial fission is mediated by AMPK activation-dependent reduction of Drp1 levels. The main serum chemical components of BYHWD, ferulic acid, and calycosin-7-glucoside, can reduce the expression of Drp1 by regulating AMPK, and can inhibit the activity of GTPase of Drp1. Conclusion: The above findings support the conclusion that BYHWD suppresses diabetes-accelerated atherosclerosis by reducing mitochondrial fission through modulation of the AMPK/Drp1 pathway. Graphical abstract: Image 1 Highlights: Buyang Huanwu decoction suppresses diabetes-accelerated atherosclerosis. Buyang Huanwu decoction attenuates endothelial dysfunction and atherosclerosis by inhibiting Drp1-dependent mitochondrial fission. Calycosin-7-glucoside and ferulic acid, two main active compounds in Buying Huanwu decoction, reduces Drp1 expression and GTPase activity.